Genome size is strongly linked to carbohydrate storage and weakly linked to root sprouting ability in herbs - Bitomský, Martin; Martínková, Jana; Lubbe, F Curtis; Marešová, Iveta; Klimešová, Jitka (Annals of botany, 2023)
BACKGROUND AND AIMS: Several lines of evidence indicate that carbohydrate storage in plant below-ground organs might be positively related to genome size because both these plant properties represent resource sinks and can affect cell size, cell cycle time, water-use efficiency and plant growth. However, plants adapted to disturbance, such as root sprouters, could be an exception because their strategy would require higher carbohydrate reserves to fuel biomass production but small genomes to complete their cell cycles faster. METHODS: We used data from a field survey to test the relationship between genome size and the probability of root sprouting ability in 172 Central European herbaceous species. Additionally, we conducted a pot experiment with 19 herbaceous species with different sprouting ability (nine congeneric pairs plus one species), and measured root non-structural carbohydrate concentrations and pools at the end of a growing season. KEY RESULTS: In the Central European flora, the probability of root sprouting ability was lower in large-genome species but this pattern was weak. In the pot experiment, both total non-structural and water-soluble carbohydrates (mainly fructans) were positively and non-linearly related to genome size, regardless of sprouting strategy. The concentrations of mono- and disaccharides and all carbohydrate pools showed no link to genome size, and starch was absent in large-genome species. The link between genome size and carbohydrate storage was less apparent at a small phylogenetic scale because we only observed a higher carbohydrate concentration in species with larger genomes for four of the species pairs. CONCLUSIONS: Root sprouters may have smaller genomes because of their frequent occurrence in dry and open habitats. Large-genome species with presumably large cells and vacuoles could accumulate more water-soluble carbohydrates at the end of the growing season to fuel their growth and perhaps protect vulnerable organs from freezing early in the next season.
Keywords: Carbohydrates; kořeny rostlin; sacharidy; cell size; Below-ground organ; root sprouting; metabolismus sacharidů; ekosystém; Plant Roots; délka genomu; Carbohydrate Metabolism; fructan; voda; Plants; carbon storage; fylogeneze; genome size; Water; Ecosystem; Genome Size; Phylogeny; rostliny